Modeling Infant i's Look on Trial t: Race-Face Preference Depends on i's Looking Style - Hoben Thomas; Ina Fassbender (Frontiers in Psychology, 2017)
When employing between-infant designs young infants' looking style is related to their development: Short looking (SL) infants are cognitively accelerated over their long looking (LL) peers. In fact, looking style is a within-infant variable, and depends on infant i's look distribution over trials. For the paired array setting, a model is provided which specifies the probability, πi ∈ [0, 1], that i is SL. The model is employed in a face preference study; 74 Caucasian infants were longitudinally assessed at 3, 6, and 9 months. Each i viewed same race (Caucasian) vs. other race (African) faces. Infants become SL with development, but there are huge individual differences in rate of change over age. Three month LL infants, π^i<1/2, preferred other race faces. SL infants, π^i>1/2, preferring same race faces at 3, and other race faces at 6 and 9 months. Looking style changes precede and may control changes in face preference. Ignoring looking style can be misleading: Without considering looking style, 3 month infants show no face preference.